Protective Effects of Beta Glucan and Gliclazide on Brain Tissue and Sciatic Nerve of Diabetic Rats Induced by Streptozosin. (16th January 2012) - Alp, Harun; Varol, Sefer; Celik, Muhammet Murat; Altas, Murat; Evliyaoglu, Osman; Tokgoz, Orhan; Tanrıverdi, Mehmet Halis; Uzar, Ertugrul
Abstract : There have not been yet enough studies about effects of beta glucan and gliclazide on oxidative stress created by streptozotocin in the brain and sciatic nerve of diabetic rats. The aim of this paper was to investigate the antioxidant effects of gliclazide and beta glucan on oxidative stress and lipid peroxidation created by streptozotosin in brain and sciatic nerve. Total of 42 rats were divided into 6 groups including control, diabetic untreated (DM) (only STZ, diabetic), STZ (DM) + beta glucan, STZ (DM) + gliclazide, only beta glucan treated (no diabetic), and only gliclazide treated (no diabetic). The brain and sciatic nerve tissue samples were analyzed for malondialdehyde (MDA), total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and paraoxonase (PON-1) levels. We found a significant increase in MDA, TOS, and OSI along with a reduction in TAS level, catalase, and PON-1 activities in brain and sciatic nerve of streptozotocin-induced diabetic rats. Also, this study shows that in terms of these parameters both gliclazide and beta glucan have a neuroprotective effect on the brain and sciatic nerve of the streptozotocin-induced diabetic rat. Our conclusion was that gliclazide and beta glucan have antioxidant effects on the brain and sciatic nerve of the streptozotocin-induced diabetic rat.